2023
DOI: 10.1111/cod.14302
|View full text |Cite
|
Sign up to set email alerts
|

Use test with l‐carvone in toothpaste on sensitized individuals

Abstract: Background: The mint flavour carvone (l-carvone) is considered a weak contact allergen. However, contact allergy to carvone is more prevalent in patients with oral lichen planus or oral lichenoid lesions (OLP/OLL).Objective: Our aim was to investigate how carvone affects sensitized individuals through a use test with toothpaste containing carvone. Non-flavoured toothpaste served as control.Methods: Subjects were patch tested prior to the use test-14 subjects allergic to carvone (11 with OLP/OLL), 20 subjects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…It is unclear whether the concentrations of carvone in toothpastes are sufficient to elicit allergic contact stomatitis in patients with oral mucosal disease 27 . However, a recent study suggests that exposure to carvone in toothpaste caused oral lesions mimicking OLP and peri‐oral eczema 28 . In our study, carvone was felt to be the main causal sensitiser in spearmint, given that almost all of the patients who tested positive to spearmint also had a positive reaction to carvone.…”
Section: Discussionmentioning
confidence: 53%
“…It is unclear whether the concentrations of carvone in toothpastes are sufficient to elicit allergic contact stomatitis in patients with oral mucosal disease 27 . However, a recent study suggests that exposure to carvone in toothpaste caused oral lesions mimicking OLP and peri‐oral eczema 28 . In our study, carvone was felt to be the main causal sensitiser in spearmint, given that almost all of the patients who tested positive to spearmint also had a positive reaction to carvone.…”
Section: Discussionmentioning
confidence: 53%
“…Some reports indicated that eugenol allergy symptoms can resemble burning mouth syndrome [190,191]. Additionally, while uncommon, some toothpaste ingredients [192], including menthol [193] and carvone [194][195][196][197], can cause dermatological issues including contact dermatitis. In line with this, a retrospective study analyzed carvone patch tests results.…”
Section: Allergic Reactionsmentioning
confidence: 99%